Pola Konsumsi Pangan Ibu Pasca Melahirkan di RSIA Thaha Bakrie Samarinda - Afrilia Sandra Ramadhani; Made Astawan; Winiati Pudji Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Food taboos are practiced in some Indonesian culture. For example there is a tendency that postpartum mother is not recommended to consume protein sources in Samarinda, East Kalimantan. The objective of this study was to evaluate food intake of pospartum mothers, including variety of food taboos which it can affect to mothers. The research involved 40 postpartum respondents, age 19-40 years. Respondents were interviewed using a questionnaire and food recall form. Analysis of data is Univariate and Bivariate analysis, bivariate analysis using chi-square stastical test with 90% level of significance (α=0.10). The result showed 65% of respondents had taboos to certain foods. The most that 80% avoided food was seafood. Factors that affect food taboos from the neigborhood and education level of respondents.